Introduction to Women’s & Gender Studies - Clemens, Colleen Lutz (Open textbook library., 2023)
Introduction to Women’s and Gender Studies (2023) is an eTextbook designed to provide an introduction to the fields of Women’s Studies and Gender Studies for students taking introductory courses. The textbook touches on a variety of subjects including gender theories, feminisms, intersectionality, equity, and activism. Chapters contain questions to consider and list of suggested readings by theorists and activists. This multimedia eTextbook incorporates videos and podcasts to create a rich introductory experience for students.